MicroRNA cluster miR199a/214 are differentially expressed in female and male rats following nicotine self-administration. Issue 1 (December 2018) - Pittenger, Steven; Schaal, Victoria; Moore, Dalia; Guda, Rahul; Koul, Sneh; Yelamanchili, Sowmya; Bevins, Rick; Pendyala, Gurudutt
Abstract Previous research has established sex differences associated with nicotine intake, however a significant gap in knowledge remains regarding the molecular mechanisms that govern these differences at the transcriptional level. One critical regulator of transcription are microRNAs (miRNAs). miRNAs are a family of non-coding RNAs that regulate an array of important biological functions altered in several disease states, including neuroadaptive changes within the brain associated with drug dependence. We examined the prefrontal cortex (PFC) from male and female Sprague-Dawley rats following self-administration (22 days) of nicotine or yoked saline controls using next generation RNA-Sequencing (RNA-Seq) technology and found an array of miRNAs to be significantly and differentially regulated by nicotine self-administration. Of these, we found the expression of miR-199a and 214, which are expressed on the same cluster of chromosome 1, to be upregulated in the female rats exposed to nicotine; upregulation in this group was further validated by real time polymerase chain reaction (RT-PCR). Bioinformatics analysis to assess common targets of miR-199/214 identified Sirtuin 1 (SIRT1), a nicotinamide adenine dinucleotide (NAD)- dependent deacetylase that plays a role in apoptosis, neuron survival, and stress resistance. Using western-blot, we confirmed downregulation of SIRT1 and increased cleaved caspase 3 expression in the brains of nicotine-exposed female rats and no change in expression levels in the other groups. Collectively, our findings highlight a miR-199/214 regulatory network that, through SIRT1, may be associated with nicotine seeking in females which may serve as a potential therapeutic target for sex-specific treatment approaches.